Irish exceptionalism? local food environments and dietary quality. Issue 10 (3rd March 2011) - Layte, Richard; Harrington, Janas; Sexton, Eithne; Perry, Ivan J; Cullinan, John; Lyons, Sean
Abstract : Objective: To explore whether distance to and density of food outlets within the local area have an impact on individual dietary quality, controlling for the socioeconomic characteristics of individuals and their households. Methods: An analysis of the Survey of Lifestyle, Attitudes and Nutrition in Ireland (SLÁN), a two-stage clustered sample of 10 364 individuals aged 18+ from the Republic of Ireland. Socioeconomic status was measured using net household income and highest level of education. Diet was assessed via a food frequency questionnaire and the results scored in terms of cardiovascular risk. Food availability was measured in terms of distance to (Euclidean and network) and density of different types of food outlets. Dietary quality was decomposed using fixed effects regression models. Results: There is a pronounced gradient in distances to nearest food store and quality of diet by socioeconomic status. Controlling for individual and household socioeconomic status and demographic characteristics, individuals who live closer to a larger food outlet or who live in an area with a higher density of larger food outlets have a significantly better diet in terms of cardiovascular risk. Conclusions: Studies outside of North America have failed to find that the physical availability of food plays a significant role in socioeconomic gradients in diet and nutrition. This study suggests that food availability in the Republic of Ireland plays a small but statistically significant role in influencing the diets of individuals and communities and, as such, may also influence socioeconomic inequalities in health.